CRYSTAL STRUCTURES OF SULFIDES AND OTHER CHALCOGENIDES - Makovicky E. (My University, 2006)
In this chapter, the crystal structures of sulfides and related chalcogenide compounds (involving Se, Te, As and Sb as well as S) are reviewed with emphasis on mineral phases but with some discussion of related synthetic compounds. Before presenting a systematic account of the principal families, relevant crystal chemical concepts are discussed, and structural classification schemes for these phases are reviewed.